Uji Mutu Refined Karaginan Dari Eucheuma spinosum Berdasarkan Perbedaan Konsentrasi Kalium Hidroksida - arto, Yanu andhi; Rakhma, Dita Nurlita; Fahmi, Nita Yunia (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2021)
Carrageenan in the pharmaceutical industry can be used as a stabilizer, thickener, gelling agent, emulsifier, and binder. Alkaline solutions such as KOH have two functions, which help extract polysaccharides to be more perfect and accelerate the elimination of 6-sulfate from the monomer unit to 3,6-anhydro-D-galactose so that it can improve the quality of carrageenan. The purpose of this study is to evaluate the effect of to determine the effect KOH of differences concentration on yield carrageenan characteristics from the extraction results Microwave-assisted extraction (MAE). The carrageenan quality parameters tested water content, ash content, sulfate content and viscosity. The Eucheuma spinosum originating from the waters of Sumenep, Madura was extracted at the Phytochemical Laboratory of Pharmacy Program, Hang Tuah University, Surabaya using different concentrations of KOH 10%, 15%, and 20% with the Microwave Assisted Extraction (MAE) method which was then filtered and neutralized with filtration and neutralized with The HCl is then precipitated with ethanol 96%, drying and grinding until to obtain a fine carrageenan is powder. The carrageenan obtained was then calculated the for yield percentage and analyzed for the water content, ash content, sulfate content and viscosity. The concentration of KOH affects % yield where an average increase in yield results along with increasing the concentration of KOH, the highest yield at 20% concentration of KOH is 37.41% Â± 1.186 and an analysis of the standard carrageenan quality test is carried out where those that meet the quality requirements are water content, ash content, and sulfate content. As for viscosity, there was no significant difference in the KOH concentrations of 15% and 20%.